Conceptual Analysis for Knowledge-Base Design - Sowa, J. F. (Methods of Information in Medicine, 1995)
Knowledge-base design requires a thorough analysis of the concepts to be represented. If the analysis is incomplete or inaccurate, the resulting knowledge base may contain arbitrary restrictions, inconsistent data, or limitations that make future extensions impossible. Conceptual analysis is even more critical for sharing knowledge bases between heterogeneous systems. Analyses that are adequate for independent systems may cause incompatibilities when the systems share data. This paper discusses the kinds of problems that require a careful conceptual analysis and the difficulties caused by an incorrect or incomplete analysis. It also shows how independently developed knowledge bases can be related to one another by reanalyzing and redefining the basic concepts and relations. Such analysis is essential for sharing knowledge between systems developed for different purposes, such as relational and object-oriented databases or expert systems and natural language processors.
Keywords: Conceptual Analysis; Conceptual Graphs; Natural Language Processing; Knowledge Base Design